Accountability of Madrasah’s Headmaster in Management of Education Financing - Sisran, Sisran (Al-Miskawaih: Journal of Science Education, 2024)
This article examines the accountability of madrasah heads in managing education financing at Madrasah Tsanawiyah Al - Islah Tanjung Jabung Timur. Derived from descriptive qualitative research, data collection in this article was carried out using observation techniques, in-depth interviews , and documentation . Research findings show that the Head of Madrasah Not yet own accountability fully in carrying out the management of madrasa financing. This can be seen from because Still many management indicators financing that has not yet been implemented. Meanwhile, effectiveness and efficiency in management financing education in madrasa already walk, However Still There is lack in a way management that must be improved. Likewise, the success of the strategy of the Head of MTs Al Ishlah Tanjung Jabung Timur, Jambi Province in meeting the educational funding shortfall has been running well in accordance with the budget plan. Artikel ini mengkaji akuntabilitas kepala madrasah dalam pengelolaan pembiayaan pendidikan di Madrasah Tsanawiyah Al-Islah Tanjung Jabung Timur. Berasal dari penelitian kualitatif deskriptif, pengumpulan data dalam artikel ini dilakukan dengan teknik observasi, wawancara mendalam, dan dokumentas. Temuan penelitian menunjukkan bahwa Kepala Madrasah belum memiliki akuntabilitas sepenuhnya dalam menjalankan pengelolaan pembiayaan madrasah. Hal ini terlihat dari karena masih banyaknya indikator pengelolaan pembiayaan yang belum terlaksana. Sedangkan efektifitas dan efisiensi dalam pengelolaan pembiayaan pendidikan di madrasah sudah berjalan, namun masih ada kekurangan secara manajemen yang harus dibenahi. Demikian juga keberhasilan strategi Kepala MTs Al Ishlah Tanjung Jabung Timur Propinsi Jambi dalam memenuhi kekurangan pembiyaan pendidikan sudah berjalan dengan baik sesuai dengan rencana anggaran.